Comunicación digital y su influencia en el aprendizaje en la Universidad Técnica de Babahoyo, Extensión Quevedo, quinto año de Comunicación Social paralelo “A”, año 2021 - Bermudez Cardenas, Mauro Emilio (2021)
The investigative work aims to study to analyze digital communication media and define how they manage to influence young students in a specific way of the Social Communication career. To make this analysis a reference is made of its incidence within the teaching-learning process of this university career, as well as outside it, that is, it is intended to make a detailed study on several aspects that are affected in various ways by these common tools that today have become essential. The university group that made up the population had an active participation in the execution of this research and expressed their intentions to learn about these media and their influence and how to make use of them as resources within the activities that exist in the professional training field. , the population is aware of the usefulness and relationship that exists between these communication tools and acting as a student of social communication, thus favoring meaningful and competent learning in the student. The development of this research work yielded good results since it aroused the interest of the students to use other useful tools such as digital media, in addition to the already known ones, it was also possible to arouse curiosity about knowing these media and motivate those involved about the importance of improving day by day in professional performance as information workers, learning about these media demands of a technologically globalized world united by the internet. The learning process in the students who would turn out to be the most benefited would have an increase in the quality of teaching offered by the institution, which would greatly benefit the entire community